Avidly Reads Passages - Commander, Michelle D., 1978- (Book collections on Project MUSE., 2021)
In Avidly Reads Passages, Michelle D. Commander plies four freighted modes of travel--the slave ship, train, automobile, and bus--to map the mobility of her ancestors over the past five centuries. In the process, she refreshes the conventional American travel narrative by telling an urgent story about how history shapes what moves us, as well as what prevents so many Black Americans from moving or being moved. Anchored in her maternal kin's long history on and alongside plantations in rural South Carolina, Commander explores her family members' ability and inability to navigate safely through space, time, and emotion, detailing how Black lives were shaped by the actual vehicles that promised an escape from the confines of American racism, yet nearly always failed to deliver on those promises. Using personal and public archives, Avidly Reads Passages unfolds distinct histories of transatlantic slavery ships, the possibilities presented by rail lines in the Reconstruction South, the fateful legacies of school busing, and the ways that Black Americans attempted to negotiate their automobility, including through the use of road and travel compendiums such as Travelguide and The Negro Motorist Green Book.